2021
DOI: 10.1002/anie.202105186
|View full text |Cite
|
Sign up to set email alerts
|

An Adjacent Atomic Platinum Site Enables Single‐Atom Iron with High Oxygen Reduction Reaction Performance

Abstract: The modulation effect has been widely investigated to tune the electronic state of single‐atomic M‐N‐C catalysts to enhance the activity of oxygen reduction reaction (ORR). However, the in‐depth study of modulation effect is rarely reported for the isolated dual‐atomic metal sites. Now, the catalytic activities of Fe‐N4 moiety can be enhanced by the adjacent Pt‐N4 moiety through the modulation effect, in which the Pt‐N4 acts as the modulator to tune the 3d electronic orbitals of Fe‐N4 active site and optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 311 publications
(202 citation statements)
references
References 83 publications
(20 reference statements)
4
178
0
Order By: Relevance
“…For example, Li et al reported that Co single-atom catalyst can be tailored and optimized by regulating atomic configuration through the modulation of P coordination atoms. [30] Han et al described the modulation effect of Pt-N 4 moiety could bestow the Fe-N 4 on high ORR performance [31]. Research demonstrates the atomic level planar architecture of metal coordinated by four nitrogen atoms supplies as the real active sites [32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al reported that Co single-atom catalyst can be tailored and optimized by regulating atomic configuration through the modulation of P coordination atoms. [30] Han et al described the modulation effect of Pt-N 4 moiety could bestow the Fe-N 4 on high ORR performance [31]. Research demonstrates the atomic level planar architecture of metal coordinated by four nitrogen atoms supplies as the real active sites [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that most carbon-supported SACs with abundant nitrogen-doped are stable activated single-metal ions to form the homogeneous microcosmic structure of M-N x -C y . The universal methods for synthesizing carbon-supported SACs include molecular skeleton encapsulation, [34][35][36][37][38] impregnation and pyrolysis, [39][40][41] coordination regulation, [42][43][44] and thermal dispersion.…”
Section: Carbon-supported Sacsmentioning
confidence: 99%
“…4d. 57 They employed zeolite imidazole frameworks (ZIF8s) as N-rich carbon precursors to generate exclusive M-N 4 active sites. Fu et al constructed atomically dispersed Cu@N 4 and Zn@N 4 on a N-doped carbon support (Cu/Zn@NC) by directly pyrolyzing a CuZn-ZIF precursor.…”
Section: Dual-atom Site Catalysts (Dacs)mentioning
confidence: 99%